Analisis Pengaruh Profesionalisme dan Budaya Organisasi Terhadap Kinerja Karyawan Pada CV. Ionix Karya National - Pahrurazi; Suyatno (JURNAL BISNIS DAN PEMBANGUNAN, 2026)
This study aims to analyze the influence of professionalism and organizational culture on employee performance at CV Ionix Karya National, a service company specializing in Apple device repairs. The research utilizes a descriptive-qualitative approach with data collection through interviews and internal performance observations. The findings indicate that while technical competence (excellence) and integrity are high, there are significant gaps in accountability, independence, and altruism among technicians. Although the company shows positive turnover growth, internal productivity in terms of quantity and timeliness remains suboptimal. Strengthening professionalism through increased accountability and self-reliance, supported by a robust organizational culture, is essential for maintaining business sustainability in the Industry 4.0 era